PREPECTORAL BREAST RECONSTRUCTION: A PRELIMINARY REPORT OF A CHILEAN EXPERIENCE IN 46 PATIENTS - Letzkus, Jaime; Río, María José del; Galté, Jorge Gamboa; Bonogato, José Manuel Lagos; Belmar, G. Alejandro; H., Andrea Sepúlveda (Mastology, 2026)
Prepectoral total breast reconstruction (PPTBR) has become a popular technique due to the many benefits observed in properly selected patients. Compared with the retropectoral implant position, PPTBR has the advantage of maintaining the pectoral major muscle in its anatomic original position, avoiding acute and chronic pain, maintaining better extremity strength and motion, and avoiding animation deformity and post-radiotherapy pectoral fibrosis. The basic principles of the technique can be used with a tissue expander or permanent implants. We present the preliminary report of 46 patients (51 breasts). In all, 20 out of the 46 patients had an association with radiotherapy; 18 of them received post-mastectomy radiotherapy and 2 received total breast irradiation on previous conservative treatment. The period of follow-up was 2–32 months, beginning in July 2019. The main surgical approach was using a lateral aspect of the inframammary fold incision. Depending on the new subdermal implant pocket width, in 20 patients, a synthetic mesh was placed. We only had two major complications: one who required reintervention due to radionecrosis and conversion to a dorsal flap plus a permanent implant, and the other who required a change into a retropectoral plane reconstruction due to wound dehiscence. No implant infection of grade 3–4 capsular contraction has been reported so far. The aesthetic result was excellent for most patients and the surgeon’s opinion, according to the Harris scale.